Water quality status of rivers in the coastal city of Manado, North Sulawesi Province, Indonesia - Lasut, Markus T; Tarigan, Adianse (AQUATIC SCIENCE & MANAGEMENT, 2014)
A study on water quality status of three riverine systems, S. Bailang (SB), S. Maasing (SM), and S. Tondano (ST), in coastal city of Manado, North Sulawesi Province, has been conducted to measure several water quality parameters, to analyse source and quality of wastewater discharge, and to assess the status of the rivers related to the water quality. Measurement of the parameters was conducted using three indicators, i.e. organic (BOD5) and in-organic (N-NO3 and P-PO4), and pathogenic microorganism (Escherichia coli [EC] and total coliform [TC]). The result showed that the level of water quality varied between the rivers. The average level of water quality (based on the observed parameters) in SB, respectively, was 0.317 mg/l, 0.093 mg/l, 2 mg/l, >2420 MPN, andÂ  >2420 MPN; in SM, respectively, was 0.029 mg/l, 1.859 mg/l, 17.7 mg/l, >2420 MPN, and >2420 MPN; and in ST, respectively, was 0.299 mg/l, 0.252 mg/l, 3.5 mg/l, >2420 MPN, and >2420 MPN. The level of water quality between the rivers was not significantly different (p>0.05), except based on the parameter of N-NO3 which was significantly different (p<0.01). The status of the observed rivers varied based on the classes of their water utilities (according to the Government Regulation of Indonesia, No. 82, 2001); mostly was "unsuitable".Â Kajian tentang status kualitas air di 3 perairan sungai di kota pesisir Manado, S. Bailang (SB), S. Maasing (SM), dan S. Tondano (ST), Provinsi Sulawesi Utara, telah dilakukan yang bertujuan untuk mengukur beberapa parameter kualitas air, menganalisis sumber dan kualitas buangan limbah domestik, dan menilai status ketiga perairan sungai tersebut. Tiga indikator digunakan, yaitu: bahan organik (BOD5), bahan anorganik (N-NO3 dan P-PO4), dan mikroorganisme patogenik (Escherichia coli [EC] dan coliform total [TC]). Hasil kajian menunjukkan bahwa tingkat kualitas air perairan tersebut berbeda-beda. Konsentrasi rerata parameter kualitas airÂ  (BOD5, N-NO3, P-PO4, EC, dan TC) di SB, berturut-turut, sebesar 0.317 mg/l, 0.093 mg/l, 2 mg/l, >2420 MPN, dan >2420 MPN; di SM, berturut-turut, sebesar 0.029 mg/l, 1.859 mg/l, 17.7 mg/l, >2420 MPN, dan >2420 MPN; dan di ST, berturut-turut, sebesar 0.299 mg/l, 0.252 mg/l, 3.5 mg/l, >2420 MPN, dan >2420 MPN. Konsentrasi kualitas air ketiga sungai tersebut tidak berbeda secara signifikan (p>0.05), kecuali parameter N-NO3 (p<0.01). Secara umum, kondisi kualitas air ketiga sungai tersebut, menurut Peraturan Pemerintah No. 82, 2001) berada dalam status â€œtidak cocokâ€ untuk peruntukannya.